2011
DOI: 10.3390/ph4050741
|View full text |Cite
|
Sign up to set email alerts
|

Protein Traffic Is an Intracellular Target in Alcohol Toxicity

Abstract: Eukaryotic cells comprise a set of organelles, surrounded by membranes with a unique composition, which is maintained by a complex synthesis and transport system. Cells also synthesize the proteins destined for secretion. Together, these processes are known as the secretory pathway or exocytosis. In addition, many molecules can be internalized by cells through a process called endocytosis. Chronic and acute alcohol (ethanol) exposure alters the secretion of different essential products, such as hormones, neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 89 publications
2
11
0
Order By: Relevance
“…In the top panel is the case of no NSI and one observes no flavor transformation until the neutrino reaches r ∼ 1000 km which is the location of the MSW H resonance. In the middle panel we switch on the NSI using δǫ n = −0.84 and ǫ 0 = 2.5 × 10 −4 and find a result similar to those of Esteban-Pretel, Tomàs, and Valle [37]. One observes a NSI-induced flavor conversion at r ∼ 40 km (which is the I resonance) and then another effect not usually seen in seen in the normal hierarchy which starts at r ∼ 150 km which we will show is the bipolar/nutation oscillations.…”
Section: Nsi Effectssupporting
confidence: 66%
See 1 more Smart Citation
“…In the top panel is the case of no NSI and one observes no flavor transformation until the neutrino reaches r ∼ 1000 km which is the location of the MSW H resonance. In the middle panel we switch on the NSI using δǫ n = −0.84 and ǫ 0 = 2.5 × 10 −4 and find a result similar to those of Esteban-Pretel, Tomàs, and Valle [37]. One observes a NSI-induced flavor conversion at r ∼ 40 km (which is the I resonance) and then another effect not usually seen in seen in the normal hierarchy which starts at r ∼ 150 km which we will show is the bipolar/nutation oscillations.…”
Section: Nsi Effectssupporting
confidence: 66%
“…The effect of sterile neutrinos in supernovae has been considered on many occasions [14][15][16][17][18][19][20][21] and neutrino magnetic moments were studied by [22][23][24][25][26]. Various nonstandard interactions of neutrinos with matter have been considered [27][28][29][30][31] in particular we mention those by Esteban-Pretel, Tomàs, and Valle [32] looking at the modification of the MSW effect in supernovae [33][34][35], and then again by Blennow, Mirizzi and Serpico [36] and Esteban-Pretel, Tomàs, and Valle [37] where the neutrino-neutrino interactions were included. These studies showed the effect of NSI is to introduce new contributions to the matter potential seen by the neutrinos with strengths (relative to the standard neutrino oscillation contribution to the potential) parameterized by a set of matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Tuma et al [11] have suggested that acetaldehyde can form adducts with the sulfhydryl groups of tubulin, the contractile protein necessary for secretion process. Diminished secretion could also be due to alcohol-induced alteration in glycoconjugate receptor, as a result of a decrease in its mRNA [45].…”
Section: Modification Transport and Secretion Of Glycoconjugatesmentioning
confidence: 99%
“…Pre-Golgi transport (from endoplasmic reticulum to Golgi) may be affected by long-term alcohol exposure due to lowered exposure of regulators and effectors of GTPases (e.g. Rab, Rac) [45]. Different studies have described ethanol-induced impairments in exocytosis, endocytosis and nucleocytoplasmic transport that are involved in intracellular traffic of glycoconjugates [45,46].…”
Section: Modification Transport and Secretion Of Glycoconjugatesmentioning
confidence: 99%
See 1 more Smart Citation